Study on the irradiation damage effect of heavy ions on carbon foil - Xu Zhiyou; Liu Yong; Zhang Junjie; Tao Zechao; Jia Hui; Zhao Huanyu; Sun Liangting (EPJ Web of Conferences)
In the high-energy mode of Booster Ring (BRing) of the High Intensity heavy-ion Accelerator Facility (HIAF), the pre-accelerated ions from the iLinac will be stripped by a carbon foil to higher charge states and then injected into the BRing. The thermal deposition and irradiation damage caused by high beam intensity and high energy deposition limit the lifetime of the foil. To ensure the stable operation of HIAF, a long-lifetime stripper foil with excellent irradiation and high-temperature resistance is required. This report aims to reveal the irradiation damage evolution of several kinds of carbon foils and its impact on their physical properties. Irradiation experiments were performed at HIRFL-SFC using Xe beams with the energy loss close to that of U beams in HIAF. There were three kinds of foils from four producer irradiated in the experiments, including Multilayer graphene (MLG) produced by KANEKA Co. and the Institute of Coal Chemistry (SXICC), diamond-like carbon (DLC) foil by the Institiute of Modern Physics (IMP) and Graphene Oxide (GO) foil by TIMESNANO Co. Various characterization methods were used to study the changes in surface morphologies, microstructures, and physical properties of the foils. The results indicated that MLG has a tendency for amorphization, DLC has a tendency for graphitization, and the oxygen-containing functional groups on the GO surface are damaged. These structural changes are expected to significantly impact the mechanical properties of the foils.